Pelatihan dan Pendampingan Pemeliharaan Ikan Lele Guna Meningkatkan Omzet Penjualan di Desa Kanigoro Kabupaten Malang - Asroful Anam; Arif Kurniawan; Teguh Rahardjo (University of Merdeka Malang, 2021)
Prosperous sociaty in terms of livelihoods and having high income to fulfill all their needs are absolute desires, so they can avoid poverty, especially for people in rural areas whose lives depend on livestock farming, such as fish farmers. To avoid poverty, people need a program to be developed their knowledge and insight, with the aim of increasing their business income, as was done by a group of catfish farmers in Kampung Coban, Desa Kanigoro, Kecematan Pagelaran, Kabupaten Malang. Improving the knowledge and insight refered to solve their problems faced, namely the high of production and long harvest period; lack of knowledge and skills on how to select superior seeds and seedlings; and the lack of knowledge and skills in profitable business management. The program activities used social interactive methods in the form of coaching or mentoring and designing their own feed making tools. Based on the results of the activities of using tools and guidance, the catfish farmers can make their own feed mixed with factory feed, and increase the income.DOI: https://doi.org/10.26905/abdimas.v6i2.5285